The unfinished saga of invasive procedures for secondary mitral regurgitation - Grinberg, Daniel; Uhlrich, William; Thivolet, Sophie; Buzzi, Rémi; Rioufol, Gilles; Obadia, Jean Francois; Pozzi, Matteo (Annals of Cardiothoracic Surgery, 2020)
Secondary mitral regurgitation (MR) is a common valvular heart disease. Its prognostic burden in patients suffering from idiopathic or ischemic cardiomyopathy (ICM) with left ventricular (LV) dysfunction/dilation has been clearly demonstrated. Severe secondary MR is associated with an increased mortality and frequent heart failure hospitalizations. Although guideline-directed medical therapy (GDMT) is the cornerstone of the management of secondary MR, a certain proportion of patients remain symptomatic. For these patients, several surgical techniques have been progressively developed during the last few decades (replacement, repair, sub-valvular apparatus interventions and other ventricular approaches). In the absence of evidence-based medicine, the benefits of these surgical procedures remains controversial, leading to a low level of recommendation in the guidelines. One way to anticipate the future is to look to the past. Recent prospective randomized trials evaluated surgical and percutaneous techniques and led to a better understanding of how best to treat this disease. In this article, we aim to describe the saga of the surgical and percutaneous treatments for secondary MR throughout the previous decades.